Determinación de la actividad de agua y PH y su relación en la actividad microbiológica de queso que se expende en el mercado central de Machala ,2014. - Arévalo Arévalo, Mirian Lorena (2014)
The fresh cheese sold at the Central Market Machala is made from unpasteurized raw milk at the artisanal level , is a cheese with high moisture content . This research aims to create an understanding of the influence of water activity and pH on microbial growth in cheeses that are sold to consumers in the Central Market Machala and set parameters that would indicate quality indices in the products we eat. The methodology for conducting the investigation are set out in the standard INEN1528 for fresh cheeses